Consumer Resource Allocation Models at the Individual Level - Batsell, Richard R. (Journal of Consumer Research, 1980)
Journal Article Consumer Resource Allocation Models at the Individual Level Get access Richard R. Batsell Richard R. Batsell Search for other works by this author on: Oxford Academic PubMed Google Scholar Journal of Consumer Research, Volume 7, Issue 1, June 1980, Pages 78–87, https://doi.org/10.1086/208795 Published: 01 June 1980 Article history Received: 01 June 1978 Revision received: 01 October 1979 Published: 01 June 1980